Emergency medical care in developing countries: is it worthwhile? - Junaid A. Razzak; Arthur L. Kellermann
Prevention is a core value of any health system. Nonetheless, many health problems will continue to occur despite preventive services. A significant burden of diseases in developing countries is caused by time-sensitive illnesses and injuries, such as severe infections, hypoxia caused by respiratory infections, dehydration caused by diarrhoea, intentional and unintentional injuries, postpartum bleeding, and acute myocardial infarction. The provision of timely treatment during life-threatening emergencies is not a priority for many health systems in developing countries. This paper reviews evidence indicating the need to develop and/or strengthen emergency medical care systems in these countries. An argument is made for the role of emergency medical care in improving the health of populations and meeting expectations for access to emergency care. We consider emergency medical care in the community, during transportation, and at first-contact and regional referral facilities. Obstacles to developing effective emergency medical care include a lack of structural models, inappropriate training foci, concerns about cost, and sustainability in the face of a high demand for services. A basic but effective level of emergency medical care responds to perceived and actual community needs and improves the health of populations.